Utilization of Different Types of Artisanal Salt in Making Padas (Siganus Species) Bagoong - Zareno, Rexian Noah Ventayen; De Vera, Amelita Miranda (Asian Journal of Multidisciplinary Studies, 2024)
This study aimed to develop a new variety of Padas (siganus species) Bagoong using Sugpo Salt from Dasol, Pangasinan, Asin sa Buy-o from Zambales, and Asin Tibuok from Bohol, and assess its sensory acceptability, microbial properties and return of expenditure. The Experimental Completely Randomized Research Design was utilized, employing a validated survey form to gather data from bagoong manufacturers, food technology experts, and food service management students. Mean, weighted means, and GLM-ANOVA were employed to analyze sensory acceptability. Treatment 2 of Padas Bagoong, containing 1 cup of Asin sa Buy O, and 3 cups of padas (siganus species) fish, received the highest overall mean and with very much liked adjectival rating. Microbial analysis demonstrated compliance with regulatory standards, with low microbial contamination levels. Padas Bagoong made with Asin sa Buy O salt exhibited the highest favorability in sensory acceptability. Microbial analysis indicated product safety, with low microbial counts. Despite variations in appearance and odor among salt types, taste consistency was observed. The study recommends further exploration of alternative salts and suggests assessing physicochemical properties and shelf life to enhance product quality control. Incorporating shelf-life assessment alongside microbial and physicochemical analyses can optimize production and bolster consumer confidence in Padas Bagoong as a safe, high-quality food product.